2015
DOI: 10.3923/jm.2015.523.532
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lipase Production by Thermo-Alkalophilic Bacillus sp. 8C

Abstract: Microbial lipases catalyzing the hydrolysis and synthesis of esters from glycerol and fatty acids are commercially important in food, dairy, detergent and leather industries. In the present study, 15 thermo-alkalophilic bacterial strains isolated from a compost soil sample were screened for lipase production in beef extract nitrate medium containing 1% tributyrin. The strain 8C, giving maximum lipolytic activity was morphologically and biochemically identified as Bacillus sp. Lipase production from strain 8C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…during purification steps. This is in contrast with the work of Bhosal et al [10] in which the aggregation caused a slight reduction in lipolytic activity during the purification step. Bhosal et al [10] reported an optimum temperature of 30°C and pH 8 lipase production by the bacterial strain isolated from oil-contaminated soil [33].…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…during purification steps. This is in contrast with the work of Bhosal et al [10] in which the aggregation caused a slight reduction in lipolytic activity during the purification step. Bhosal et al [10] reported an optimum temperature of 30°C and pH 8 lipase production by the bacterial strain isolated from oil-contaminated soil [33].…”
Section: Resultscontrasting
confidence: 98%
“…Also, they are less affected by seasons and the climate [8]. Bacteria lipase is usually extracellular and is greatly influenced by nutritional and physicochemical parameters such as temperature, pH etc [9][10]. Lipases of microbial origin are more stable than plant and animal enzymes and their production is more easy, convenient, safer and cheaper [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bhosale et al . () reported that the lowest enzyme productivity by thermo‐alkalophilic Bacillus sp. 8C was recorded in the presence of xylose.…”
Section: Discussionmentioning
confidence: 99%
“…Mazhar et al (2017) reported optimum lipase production by Bacillus subtilis PCSIRNL-39 within 72 h, however, Dannert et al (1997) reported optimum lipase production by B. thermocatenulatus within 16 h. Skhon et al (2006) reported maximum lipase production by B. megaterium AKG-1 in the presence of peptone after 27 h of incubation at pH 7Á5 and in contrast to this study, glucose, xylose and sucrose decreased its lipase productivity. Bhosale et al (2015) reported that the lowest enzyme productivity by thermo-alkalophilic Bacillus sp. 8C was recorded in the presence of xylose.…”
Section: Discussionmentioning
confidence: 99%
“…While the study of [33][34][35] were reported the incubation temperature at 25°C was gave the maximum lipase production for Pseudomonas spp., While the study of 36 whose exhibited that 40°C the maximum lipase production for Pseudomonas cepaciea was at 40°C. and the study of 37,38 reported that incubation temperature at 50 C was optimum temperature for production of lipase by Bacillus sp. 8°C.…”
Section: Determination Of Lipase Activitymentioning
confidence: 95%